Nullspace Control for Automatic Ultrasound Gel Supply - Osburg Jonas; Ernst Floris (Current Directions in Biomedical Engineering)
Ultrasound gel is used as a coupling medium in ultrasound procedures, thereby ensuring the entry of sound waves into the body of the patient and providing ultrasound images of high quality. In this paper, we present an approach to automatically supply ultrasound gel during robot guided ultrasound examinations. For this purpose, we combine a simple mechanical design consisting of a gel tube and a push mechanism with a specialized control strategy exploiting the robotic nullspace of 7 DoF redundant manipulator. Functionality is demonstrated by robotic ultrasound scans on phantoms, with gel being automatically applied when needed.